KARAKTERISTIK SOFT-CRUST TART NON-GLUTEN BERBASIS UBI UNGU DAN TEPUNG MOCAF - Rifatul Masrikhiyah; Ratu Diah Koerniawati; Widia Pangestika (Program Studi Ilmu Teknologi Pangan Universitas Muhadi Setiabudi, 2026)
Dietary fiber consumption among the Indonesian population remains low compared to the Recommended Dietary Allowances (RDA). This study aimed to develop a functional non-gluten food product in the form of soft-crust tart based on purple sweet potato (Ipomoea batatas L.) and Modified Cassava Flour (MOCAF) and to compare its physical, sensory, and nutritional characteristics. The research method utilized an experimental design with two variations of crust formulation: P1 (Full Purple Sweet Potato Crust 500 g) and P2 (Purple Sweet Potato Crust 500 g + MOCAF Flour 50 g). Tested parameters included physical attributes (color and texture), sensory quality via a hedonic test by 25 panelists, and nutritional estimation using NutriSurvey software. The hedonic test results revealed that formulation P1 achieved a higher overall acceptance score of 4.35 compared to P2 with 3.82. Panelists significantly preferred the flavor (4.44) and texture (4.24) of P1 due to the optimal natural softness of purple sweet potato starch. Nutritionally, P1 yielded 1155.7 kcal and 7 g of fiber per recipe, while P2 yielded 1330.7 kcal and 13 g of fiber. It is concluded that formulation P1 is the optimal treatment for physical and sensory parameters, whereas P2 is superior in terms of dietary fiber content.